SKT Meditation Therapy Model by SKT Trainers for Controlling Blood Pressure in Hypertensive Patients, Yasothon Province. - กวีกรณ์, ประชุมพร; แสงสว่าง, ภูเบศร์; ค้าข้าว, เนาวรัตน์; ครองยุติ, เพชรสุดา (Journal of Preventive Medicine Association of Thailand, 2018)
Nowadays, patients with hypertension are not able to control their blood pressure levels to be within the normal range. This leads to many complications and the number of these patients has increased. The Guidelines in currently for controlling high blood pressure is not possible to reduce it because the patients behavior are not continuous or intermittent and the methods were approved is not suitable to the lifestyle of them. Now healing meditation is using with drug therapy when the effective can reduce the stress and lower blood pressure. Therefore, this study was aimed to 1) Develop a meditation SKT Model by SKT trainer to control blood pressure in patients with hypertension at Yasothon. 2) To compare levels of blood pressure, BMI, Cholesterol, LDL Triglyceride and Creatinine before and after Meditation SKT Model, and 3) to evaluate the level of satisfaction in the practice of meditation therapy group. This study design was a research and development (R&D) studies between May-July 2015. The 36 subject consisted of patients: who could not control blood pressure was purposive random sampling. The measurement were used SKT trainer, questionnaire, laboratory, measuring blood pressure and the self-recode at home of SKT. The data were analyzed by using standard descriptive statistics and statistical pair t-test to compare between before and after, the average of blood pressure, BMI, Cholesterol, LDL, Triglyceride Creatinine but the quality data was analyzedon the content of objectives. The result, most of subjects were female (55.6%), 36.1% of aged between 46-60 years, 61.1% were elementary, the occupation was agriculture (69.4%), 66.7% were married and 52.8% had hypertension for 1 to 5 years. The problems of patients with hypertension high blood pressure can not be controlled. The majority of systolic levels is 88.9% at 140-159 mmHg and diastolic levels is 94.4% at 90-99 mmHg. SKT model for control blood pressure in patients had to training course SKT standard for trainers about 3 days before they had going to teach the subjects and assign the patients to do SKT continuously at their home every day for 8 weeks with to receive a visit from a trainer, Output of SKT meditation the mostly 58.3% were regularly practice, meditation two times per day, 63.9% and 36.1% to approximately 15-20 minutes per session, posture. 83.3% to practice the position 1,75.0% do SKT in the wake up or early morning, 41.7% have been visited 3-4 times, 58.3% the health is much improved more healthy, and 86.1% were satisfied with the performance of SKT meditation. Issue hurdles in the meditation is not uniform or practice at one position mostly, affecting for hyper tension is not ensured but it is good for the health for example muscle, gastrointestinal, excretion, sleep or weight of body. In comparison between before and after the operation showed the average of blood pressure Systolic and Diastolic, BMI, Cholesterol, LDL, Triglyceride and Creatinine, after do SKT at the end of the study found the last mean of all were decrease from before practice SKT statistical significance (Mean Difference=22.56, 18.33, 0.61, 12.58 and 0.12; 95% CI=18.98-26.13, 15.74-20.92, 0.24-0.98, 4.07-21.09 and 0.07-0.17; P-value <0.001,. <0.001, 0.002, 0.005 and <0.001, respectively). The recommend, by using “meditation healing,” the public health services should select patients that love to practice meditation and would be willing to volunteer. The meditation healing method called “SKT” is recommended along with other methods in controlling blood pressure levels.